Risk factors for, metrics of, and consequences of access to veterinary care for companion animals: A scoping review - Annette O’Connor; Sarah Ceridwen Totton; Michelle Hernandez; Emily Meyers; Kelley Meyers; Hilda Mejia Abreu; Nathaniel Spofford; JoAnn Morrison (PLoS ONE, 2025)
Background Barriers to accessing veterinary care can be challenging for companion-animal caregivers and may lead to preventable health conditions or even death of pets. Objectives We conducted a scoping review to: 1) catalog the definitions of access to veterinary care (A2VC) used by researchers, 2) identify risk factors for and consequences of A2VC, and 3) map the risk factors onto dimensions of access to care (affordability, availability, accessibility, accommodation, acceptability). Eligibility criteria Primary research on companion animals not involved in commercial enterprises (e.g., horse racing) examining consequences of and/or risk factors for A2VC for which the full text was available in English. Sources of evidence PubMed (1996–6 July 2023) and CAB Abstracts (1973–13 July 2023, Web of ScienceTM) were searched. Additionally, a topic expert (KM) identified relevant references. Two reviewers independently screened titles/abstracts and full texts of potentially relevant references. Forward and backward citation searches were also conducted on all eligible studies using Citation Chaser. Charting methods Risk factors were categorized and mapped to the five dimensions of access to care. An evidence gap map was created using the risk factor studies. Results Fifty-one references describing fifty-two relevant studies were included. Forty-one studied risk factors associated with A2VC, and twelve studied consequences of A2VC. (One study examined both risk factors and consequences.) The majority of risk factors examined were demographic. The majority of outcomes measured were pet-centric. No relevant studies focused on pet horses, representing a gap in the literature. Conclusions Consensus needs to be reached on how A2VC is defined and measured to help reduce research wastage and strengthen impact of future studies on improving A2VC. Future studies of risk factors for A2VC should focus on creating a risk-mapping framework specific for A2VC, distinguishing factors that are susceptible to change and those which are not.